Seismo-electrics, electro-seismics, and seismo-magnetics for earth sciences - Jouniaux, Laurence (2015)
The seismo-electromagnetic method (SEM) is used for non-invasive subsurface exploration. It shows interesting results for detecting fluids such as water, ice, oil, gas, CO2, and also to better characterise the subsurface in terms of porosity, permeability, and fractures. However, a limitation of this method is the low level of the induced signals. We first describe SEM's theoretical background, and the role of some key parameters. We then detail recent studies on SEM, through theoretical and numerical developments, and through field and laboratory observations, to show that this method can bring advantages compared to classical geophysical methods.